2022
DOI: 10.1007/s13304-022-01272-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of scoring systems regarding the gender as a parameter with the traditional scoring systems for predicting appendicitis

Abstract: Although acute appendicitis remains the most common cause of acute abdomen in General Surgery practice, negative appendectomy rates are still high in particularly female patients. Appendicitis scoring systems considering gender can help the clinician to reduce negative appendectomy rates in females. This present study aims to compare the Lintula, Ripasa, Fenyo-Lindberg scoring systems, which use gender as a variable, with the Alvarado, Karaman, scoring systems to evaluate which CSS is more successful in the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 17 publications
0
7
0
1
Order By: Relevance
“…Similarly, Albahadili MA et al 15 reported that the mean age of the patients of acute appendicitis was 27.44 years, males were 56% and females were 44%. Inconsistently Capoglu R et al 16 reported that females were in majority 52.6% and males were 47.4%. On the other hand, Memon SN et al 17 demonstrated that the average age of the patients was 21.25±9.12 years and males were in majority 62%, while females were 38%.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Similarly, Albahadili MA et al 15 reported that the mean age of the patients of acute appendicitis was 27.44 years, males were 56% and females were 44%. Inconsistently Capoglu R et al 16 reported that females were in majority 52.6% and males were 47.4%. On the other hand, Memon SN et al 17 demonstrated that the average age of the patients was 21.25±9.12 years and males were in majority 62%, while females were 38%.…”
Section: Discussionmentioning
confidence: 90%
“…Since the Alvarado score is the first created for acute appendicitis and also has repeatedly been proved to be appropriate, almost several newer clinical scoring systems are evaluated against it. [21][22][23]…”
Section: Discussionmentioning
confidence: 99%
“…This difference shows that the scoring systems whose validity and reliability have been revealed by various well designed studies should be preferred when choosing the appendicitis scoring system for the diagnosis of acute appendicitis. Almost all novel CSSs are compared to the Alvarado score, as it was the first CSS developed for acute appendicitis and has frequently been shown to be accurate [ 1 , 15 , 28 , 31 , 34 , 35 ]. In our study, the most effective CSS in the 18–45 years age group was the Alvarado score, which was also the second most accurate scoring system (after the Fenyo–Lindberg CSS) among patients of all ages.…”
Section: Discussionmentioning
confidence: 99%
“…En consecuencia, la evidencia disponible indica que, al comparar ambas escalas, RIPASA muestra una mayor exactitud diagnóstica que . También se identificaron investigaciones que no encontraron diferencias entre ambas escalas (28)(29)(30); lo que concuerda con los hallazgos de esta investigación, en la que, ambas escalas, demostraron un rendimiento "discreto" con sensibilidad y especificidad bajas.…”
Section: N(%)unclassified